2023
DOI: 10.1177/08445621231152959
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Nursing Leadership and Patient Readmission Rate: A Systematic Review

Abstract: Background Nurse leaders play a fundamental role in improving patient quality care delivery, thus improving patient clinical outcomes. Purpose This systematic review examined the knowledge to date of nursing leadership on reducing patient readmission rates. Methods A literature review was conducted using seven electronic databases: Medline Ovid, PubMed, Cumulative Index to Nursing and Allied Health (CINAHL) Plus, Emerald, PsycINFO, ABI/INFORM collection, and EBSCO, with the addition of references for relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The evidence showed that care managers played a vital role in communicating the conditions of patients with heart failure to the interdisciplinary team. 27 , 31 The care manager can communicate the audit results to all involved stakeholders to reduce the delay and find effective practical solutions.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence showed that care managers played a vital role in communicating the conditions of patients with heart failure to the interdisciplinary team. 27 , 31 The care manager can communicate the audit results to all involved stakeholders to reduce the delay and find effective practical solutions.…”
Section: Discussionmentioning
confidence: 99%
“…No studies in this review tested these areas. The fact that only one study (Labrague, 2021a(Labrague, , 2021b Previous reviews of leadership studies concluded that working with effective leaders may effectively reduce the incidence of adverse events and missed care while improving patient and family satisfaction (Al Sabei and Ross, 2023;Lee et al, 2023;Wong et al, 2013). Therefore, toxic leadership could also negatively influence patient safety outcomes.…”
Section: Implications For Leadership Researchmentioning
confidence: 99%
“…The ongoing global crisis brought on by the COVID-19 pandemic, along with other constraints, including budget cuts, shortage of qualified nursing staff and the aging population, have further highlighted the importance of having a leader who can effectively lead and navigate the organization (James and Bennett, 2022). Mounting evidence has shown that a leadership style that places a premium on “people” or “relationships,” such as the authentic and transformational leadership styles, is more likely to have positive consequences on nurses, patients and organizations (Al Sabei and Ross, 2023; Cummings et al , 2021). Ineffective leadership styles, such as abusive and destructive leadership styles, have been strongly tied to reduced work effectiveness and poor care quality ratings (Niinihuhta and Häggman‐Laitila, 2022; Shih et al , 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Aside from managing the impact of the recent pandemic, hospital administrators have faced challenges in sustaining an effective nursing workforce (Kurtzman et al , 2022), retaining experienced and skilled nurse managers (Gaffney, 2022), and, most importantly, attracting more nurses who are motivated and willing to take leadership positions (Hardesty et al , 2018). Without stable nursing leadership, organizational success might be compromised (Cummings et al , 2021), and the continued shortage of nurse managers and leaders may negatively impact patient outcomes (Al Sabei and Ross, 2023). Despite efforts to attract a pool of nurses who can fill formal nursing leadership positions, available research has shown that fewer than 50% of nurses are inclined to these positions (Al Sabei et al , 2019; Faller and Gogek, 2019).…”
Section: Introductionmentioning
confidence: 99%